Reproducibility and transparency: what’s going on and how can we help (Nature Communications)
Problems with experimental reproducibility affect every field of science. However, the opinions on the causes of the reproducibility “crisis” and how we all can help vary amongst fields as well as individual scientists. Here, we talk to experts from different fields of science to get their insights on this endemic issue. Professor Brian Nosek is a social psychologist at the University of Virginia and executive director of the Center for Open Science. Professor Christine Mummery is a developmental biologist at Leiden University Medical Center and the former President of the International Society of Stem Cell Research. Dr Leonardo Scarabelli is a chemist and group leader at the University of Cantabria. Professor Vitaly Podzorov is a physicist at Rutgers, the State University of New Jersey, and current Donald H. Jacobs Chair in Applied Physics.